Children’s participation in the design of digital artifacts in rural schools - Morais, Dyego; Falcão, Taciana Pontual; Tedesco, Patrícia (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2022: Anais do XXI Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2022)
The definition of Participatory Design (PD) includes a valid preoccupation with power balance between designers and target users in decision-making, which researchers and practitioners still struggle to attain. The situation is more critical when design involve vulnerable groups, like children. Children’s contributions in design processes are often regarded as less valid, or unreasonable. Studies that apply PD with children often do it superficially, not taking into account the particularities of children’s behavior and the dynamics of their interaction with adults. In this sense, models and frameworks of child participation can give a more solid theoretical framing for PD with children. In this paper, we propose a theoretical model which draws from theories of child participation, for supporting PD with children. Then, we discuss the application of this model for qualitative analysis of a design process of digital educational artifacts with children from rural schools in Brazil. We perceived a focus on the co-creation of artifacts, but also a tendency of adults to assume a professorial attitude, undermining children’s autonomy on project decisions. We also observed that cultural context and school rules have a strong impact on children’s self-efficacy, limiting them to roles with less decision power. The results of applying the model to data analysis feed into planning of PD activities with children, helping researchers and designers to employ methods that promote their autonomy and participation.